Mikhalkov: cinema e ideologia frente ao desmoronamento soviético - Freitas, Rodrigo Inácio (2019)
Anna, a Russian film directed by Nikita Mikhalkov, released in 1993 and shot over more than a decade under the effectuation of Glasnost and Perestroika policies, portrays in its shape and content the political landscape that was drawn in the Socialist Bloc during the transition from the 80’s to the 90’s, the consequent redirection of economy and the changes in behavioral patterns to a Western-style consumer society effecting the landslide (Hobsbawm) of established structures. Made during this political, economical and cultural transformation era, the film reports contemporary facts but conditions them by the consensus (Benjamin) to the successive regime. The director conducts his young daughter’s interviews in order to present the replacement of the Socialist model as an evolution achieved according to him through a popular struggle against tyranny. This research intends to draft a formal analysis of the film, intrinsically related to the political, cultural and socioeconomic conjuncture in micro and macro scales and to the director’s inclinations, and it aims to present the liberalization and openness phenomenon as an imprisonment in the structures of global capitalism, corporate mercantilism (Chomsky), consensus politics, capitalism as cult and religion (Benjamin) and one-dimensionality of the contemporary human being (Marcuse) ruled by the absence of critical thought, alienation and consume.